Community Assistance in Understanding Criminal Liability for Environmental Damage in Babakan Village, Setu District, South Tangerang City - Andi Irawan; Andri Oktavianhady; Ayundati Sekar Seruni; Chairil Meivandri Adlan Tanjung; Herlina Basri (Yayasan Daarul Huda Kruengmane, 2026)
The Community Service Program (PKM) entitled “Community Assistance in Understanding Criminal Liability for Environmental Damage in Babakan Village, Setu District, South Tangerang City” aims to improve public understanding and legal awareness regarding environmental protection and the criminal consequences of environmental damage. The main problem identified is the low level of legal literacy among the community, particularly concerning environmental violations and criminal liability arising from intentional or negligent actions. The program was carried out through stages of preliminary survey, training, mentoring, and evaluation using a participatory approach that actively involved the community. The materials presented included environmental damage, environmental crimes, legal responsibility, and the role of the community in maintaining environmental sustainability. The results show an increase in public understanding of environmental law, improved legal awareness, and the development of more responsible and environmentally conscious attitudes. In addition, the community became more capable of identifying actions that may cause environmental damage and taking preventive measures in daily life.